A prospective trial of CONfocal endomicroscopy in CYSTic lesions of the pancreas: CONCYST-01 - Keane, Margaret G.; Wehnert, Natascha; Perez-Machado, Miguel; Fusai, Giuseppe K.; Thorburn, Douglas; Oppong, Kofi W.; Carroll, Nicholas; Metz, Andrew J.; Pereira, Stephen P. (Endoscopy International Open, 2019)
Background and study aims Pancreatic cystic lesions (PCL) are common. While some harbor malignant potential, accurate preoperative diagnosis remains challenging. Needle-based confocal laser endomicroscopy (nCLE) via a 19G FNA needle enables real-time imaging of the cyst wall. This study evaluated the safety and utility of nCLE in patients with an indeterminate PCL undergoing EUS-FNA.Patients and methods The CONCYST study prospectively recruited patients with indeterminate PCL attending three hepatopancreaticobiliary (HPB) referral centers in the UK, with indeterminate PCL, who required EUS-FNA between July 2014 and October 2016. Following the procedure, all patients were followed up in telephone clinic for at least 12 months. Ethical approval for the study was granted by the National Research Ethics Service (14/LO/0040).Results Sixty-seven patient were recruited, 11 excluded and 56 included in the final analysis: 35 male, 21 female; median age 68 (range 28 – 80). Recognizable confocal images were obtained in 48 of 56 cases. Median nCLE scanning time was 5 minutes and did not exceed 10 minutes in any case. EUS-nCLE findings correlated with final diagnosis (based on imaging, cytology and multidisciplinary team review) in 43/56 (77 %) of cases, compared with 37/56 (66 %) for cytology alone (P = 0.12). One patient experienced mild pruritus following the procedure and another developed an infected pseudocyst, which resolved with antibiotics.Conclusions EUS-nCLE under conscious sedation in the day case setting is safe and provides additional information to standard EUS-FNA for diagnosing indeterminate PCL.